Desafios da pós-graduação em Psicologia no Brasil - TOURINHO, Emmanuel Zagury (2011)
The regulation of Graduate Programs in Brazil is less than five decades old. Along this period, the system has been successful concerning its results, even though some of its essential features remain unfinished. In the field of Psychology, the system comprises 64 Programs and 42 of them offer Doctoral degrees. In order to efficiently cope the demands of the Brazilian Graduate System, the Psychology area will need to face challenges, some of which we highlight in this paper. They are: (a) the enlargement of geographical and thematic scope in order to overcome regional asymmetries and thematic gaps in psychological research;(b) the improvement of the evaluation system in order to comprise the diverse strategies in instructing new researchers and the knowledge production in every subarea of Psychology; (c) the necessity of a link among different areas of Graduate Programs in Psychology since the basis for knowledge production in this field may have additional demands related to the development of intervention technologies; and (d) the elaboration of policies which may qualify the system, improving the research networks, providing international exchange for the groups, promoting scientific publications, and extensive methodological learning, for instance. The diagnosis of these and other challenges, in their multiple dimensions, may lead to a more efficient use of the potentials of Brazilian research groups, towards the development of knowledge production and training new researchers.